Influence of Home Freezing and Storage on Vitamin C Contents of Some Vegetables - Tosun, B. Nursal; Yucecan, S. (Pakistan Journal of Nutrition, 2007)
Okra, potatoes, green beans, broccoli, spinach and peas were included to determine the vitamin C levels of home freezing with the impact of processing and storage. Firstly, a preliminary study was done to find the high quality vegetables (in terms of Vitamin C) for freezing, then selected vegetables were prepared for freezing according to the appropriate nutritional principles and frozen. In the second phase, all frozen vegetables kept in the freezer (6 months) to evaluate the storage effects. Vitamin C analyses were conducted just after the pre-freezing operations that may cause Vitamin C destruction, freezing and storage (3. and 6. months). Spectrophotometric method (2,6-dichlorophenol indophenol) was used to determine the vitamin C levels. Depending on the vegetable type, pre-freezing operations caused 30.9-48.0% decrease in the initial vitamin contents. Home freezing alone did not make any significant difference, but 6 months of storage resulted a total of 42.4 (green beans) - 66.5 (broccoli) % decrease.